1992
DOI: 10.1192/bjp.161.5.694
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder and Paraphilia in a Monozygotic Twin Pair

Abstract: We report OCD and paraphilia in two male members of triplets (the two males being monozygotic twins), and discuss the possible aetiological factors for this previously unreported occurrence. We suggest that patients presenting with paraphilia should be examined for OCD and that a detailed sexual history should be obtained in all patients with OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…The theoretical implications of cerebral palsy, deafness, mutism, and epilepsy in the sample remain unexplained in the present state of knowledge. Cryan et al [51] presented a pair of monozygotic twins concordant for both OCD and paraphilia and suggested there may be an organic basis to these conditions, quoting case reports of deviant sexual behavior associated with brain pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical implications of cerebral palsy, deafness, mutism, and epilepsy in the sample remain unexplained in the present state of knowledge. Cryan et al [51] presented a pair of monozygotic twins concordant for both OCD and paraphilia and suggested there may be an organic basis to these conditions, quoting case reports of deviant sexual behavior associated with brain pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Segregation analyses of OCD families based on either OCD diagnosis or OC symptoms found results most consistent with a complex genetic model, including a possible major single locus, most often in combination with multiple other minor contributing loci, suggestive of a mixed model of inheritance [31,[33][34][35][36][37]. In a still-limited number of studies, monozygotic twins have been reported as strongly concordant for OC symptoms [38][39][40][41]. Although reports contrasting the rates of the disorder in monozygotic versus dizygotic twins with OCD are few in number, in the Maudsley twin register, the concordance rates in monozygotic and dizygotic twin pairs were 87 per cent and 47 per cent, respectively, giving a heritability estimate of 80 per cent [42], and a Japanese study found concordance for OC symptoms in 80 per cent of monozygotic twins compared with 50 per cent of dizygotic twin pairs [43].…”
Section: (C) Family and Twin Studiesmentioning
confidence: 93%
“…6 The role of heredity in OCD has long been suspected by clinicians. [7][8][9][10][11] Several twin studies have found that the concordance for obsessive-compulsive symptoms is substantially greater in monozygotic twin pairs (80%-87%) than dizygotic twin pairs (47%-50%). 12,13 Many family studies of OCD have been conducted, although most had methodological limitations, such as failure to use structured or semistructured diagnostic instruments and noninclusion of control groups.…”
mentioning
confidence: 99%